2021
DOI: 10.4209/aaqr.210117
|View full text |Cite
|
Sign up to set email alerts
|

Filtration Performance of Layering Masks and Face Coverings and the Reusability of Cotton Masks after Repeated Washing and Drying

Abstract: In this study, filtration efficiency of different respirators, face masks, and a 2-ply cotton handkerchief bandana was compared for particles in the size range of 60 nm-4 μm under a "perfect fit" condition. The filtration efficiency at the most penetrating particle size of 0.3 μm on average ranged from 83-99% for N95 and KN95 respirators, 42-88% for surgical masks, 16-23% for cloth masks, and 9% for bandana. We also investigated the effects of using double surgical masks or layering a cloth mask over various s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 21 publications
3
28
0
2
Order By: Relevance
“…Konda et al 13 found filtration efficiencies of 9% and 18% for (complete single layers of) woven fabrics of 80 and 160 TPI. Sankhyan et al 15 also found similar values.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Konda et al 13 found filtration efficiencies of 9% and 18% for (complete single layers of) woven fabrics of 80 and 160 TPI. Sankhyan et al 15 also found similar values.…”
Section: Discussionmentioning
confidence: 61%
“…Both groups find a large variability in filtration efficiency from one material to another, with filtration efficiencies in the range less than 10% to almost 100%, for particles with diameters of a few micrometers. Sankhyan et al 15 found comparable filtration efficiencies to Konda et al and Duncan et al They also found that the fabric masks were systematically less good at filtering than non-woven surgical masks.…”
Section: Results For Particle Filtrationmentioning
confidence: 81%
See 3 more Smart Citations